Effect of insulin glargine on recreational physical activity and TV viewing: Analysis of the randomised ORIGIN trial. (October 2017) - Yates, Tom; Davies, Melanie J.; Jung, Hyejung; Bosch, Jackie; Spinas, Giatgen A.; Sreenan, Seamus; Commerford, Patrick; Gerstein, Hertzel C.; ,
Highlights: Weight gain is both a consequence and a cause of physical inactivity and sedentary behaviour. Insulin glargine causes modest weight gain in the management of dysglycaemia, or TV viewing. Insulin glargine was not associated with changes in recreational physical activity. Abstract: Aims: To quantify whether insulin therapy, and concomitant weight gain, affects recreational physical activity and TV viewing time using data from the Outcomes Reduction with an Initial Glargine Intervention (ORIGIN) trial. Methods: 12, 537 insulin-naïve individuals with dysglycaemia were randomised to receive either basal insulin glargine or standard care and followed for a median of 6.2 years. Complete recreational physical activity and TV viewing time questionnaires across baseline, 2 year follow-up and study end were available for 8954 participants. Differences between groups at follow-up were assessed by analysis of covariance. Results: At follow-up, there was no difference in physical activity or TV viewing time between those taking insulin glargine and those receiving standard care, despite body weight increasing by 1.66 (7.56) kg in the insulin glargine group and reducing by −0.65 (7.90) kg in the standard care group (P < 0.001). The dose of insulin glargine was not associated with changes in physical activity. Conclusions: Despite modest weight gain, insulin glargine did not adversely impact recreational physical activity levels within an international cohort with dysglyaemia. ORIGIN ClinicalTrials.gov number:NCT00069784